The Influence of Multidimensional Service Quality, Perceived Value, and Customer Relationship Management on Customer Satisfaction: The Mediating Role of Customer Engagement at Awal Care Veterinary Clinic - Mirjawal Mirjawal; Suryono Efendi; Tri Waluyo (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of Multidimensional Service Quality, Perceived Value, and Customer Relationship Management (CRM) on Customer Satisfaction, with Customer Engagement as a mediating variable at Awal Care Veterinary Clinic in East Jakarta. The research background is driven by a significant decline in patient numbers in 2023 and intense competition in the veterinary healthcare sector. This study employs a quantitative correlational approach using purposive sampling, involving 310 respondents who are clients of the clinic. Data were collected through a questionnaire with a 6-point Likert scale, and analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results indicate that all independent variables service quality, perceived value, and CRM—have a positive and significant influence on both customer engagement and customer satisfaction. Customer engagement is also found to have a significant impact on customer satisfaction. Furthermore, all indirect relationships through the mediation of customer engagement are significant, indicating that customer engagement serves as an important partial mediator. The R² value of 0.646 demonstrates that the model has strong predictive power for customer satisfaction. These findings highlight the importance of strengthening experience-based strategies and fostering emotional and cognitive connections with customers. This study contributes theoretically to the field of service marketing and provides practical implications for veterinary clinic management in enhancing customer satisfaction and loyalty.